ChemInform Abstract: Concise Synthesis of Enantiomerically Pure (1′S, 2′R)‐ and (1′R, 2′S)‐2S‐Amino‐3‐(2′‐aminomethyl‐cyclopropyl)propionic Acid: Two E‐Diastereoisomers of 4, 5‐Methano‐L‐lysine. Issue 9 (4th March 2014) - Altamore, Timothy M.; Nguyen, Oanh T. K.; Churches, Quentin I.; Cavanagh, Kate; Nguyen, Xuan T. T.; Duggan, Sandhya A. M.; Krippner, Guy Y.; Duggan, Peter J.
Abstract The zinc‐mediated cyclopropanation of E‐allylic alcohol (II) is the key step in the synthesis of methano‐L‐lysine derivatives (IV) and (V).